Pericardial Effusion as A Clue to The Diagnosis of Systemic Lupus Erythematosus - Zhafirah Ramadhanty; Teuku Rahadiyan (Journal of Agromedicine and Medical Sciences, 2023)
Pericardial effusion (PE) is accumulation of fluid in the pericardial sac. There are broad etiologies of PE, such as inflammation, infection, and malignancy. The etiology must be discovered because the treatment will be focused based on the cause. We present a 40-year-old female who came to the cardiology clinic with exertional dyspnea as the only symptom. The patient had a history of unspecific joint pain two months prior. Physical examination, chest x-ray, and electrocardiography revealed no specific findings. However, on echocardiography, we found moderate circumferential pericardial effusion. The patient then admitted for further evaluation. Blood counts, peripheral blood smear, urinalysis, and immunoserology examination such as ANA and anti-dsDNA was ordered and the result led to the diagnosis of systemic lupus erythematosus (SLE). High dose steroid injection was given for five days and the symptoms disappeared. Follow-up echocardiography after a week of hospital admission revealed significant reduction of pericardial fluid.